Accentism: English LX users of migrant background in Australia - Dryden, S.; Dovchin, Sender (2021)
Using Linguistic Ethnography (LE), we analyse the ways in which English as an additional language (LX) users from migrant backgrounds in Australia encounter overt and covert ‘accentism’ from the dominant English-speaking Australian society. These forms of accentism may be used to discriminate against LX users’ pronunciation and accent in a bid to conform, normalise, contest, and encourage unequal power. Overt accentism is used to reinforce stereotypes and ideologies about the culture, race, ethnicity or gender of the LX users on the receiving end, using mockery, laughter, and sexualisation to denigrate and stigmatise their accents. Covert accentism occurs in a subtle and indirect way when LX users may feel social exclusion by strong local accents, or through locals misunderstanding migrants’ non-standard English accents. Consequently, these participants often experience feelings of embarrassment, frustration, and loss of confidence. Accentism can also lead to problems with employment, maintaining relationships with local Australians, and exclusion from social situations. We show that these accentism experiences are intersectionally linked with race, ethnicity, nationality and gender, all of which are affected by the broader cause of structural racism, that discriminates against English LX migrants with these identity attributes.